Drum drying of unpeeled green banana pulp (Musa cavendishii) for bake stable fruit filling production. - MENDES, Mário José Andrade; IZIDORO, Dayane Rosalyn; SCHEER, Agnes de Paula (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2019)
There is a growing interest in food matrixes for the use of flour from unpeeled green banana in order to reduce waste in the production chain. Considering this, the present paper aims to studying the application of unpeeled green banana flour in the cold process performed to obtain bake stable fruit filling. The unpeeled green banana pulp (Musa Cavendishii) was dried using a single rotating drum, thus obtaining the flour. The dried flour was then analyzed for its chemical composition, amylose and resistant starch content, water absorption capacity and pasting properties. The drying reduced the amount of resistant starch and produced pregelatinized starch. The obtained flour showed physical and nutritional characteristics which enabled the development of the filling formula by using a central composite design combining levels -1 and +1, two axial points (± α), two central points, and chemical composition, water activity, Brix, and texture as response variables. The amount defined by central-composite design of unpeeled green banana flour, modified starches and other ingredients resulted in an elastic, viscous, bake stable fruit filling.